دور التكلفة المستهدفة وتحليل القيمة في تخفيض تكلفة المنتج: دراسة حالة شركة «HONDA LAIT» بالمسيلة - بوريش، مهني; امحمد، بن البار (جامعة إبراهيم سلطان شيبوط الجزائر 3, 2021)
يهدف هذا البحث إلى إبراز دور تطبيق طريقتي التكلفة المستهدفة وتحليل القيمة في تحقيق التخفيض الحقيقي لتكلفة المنتجات، بالتطبيق على شركة «HODNA LAIT» بالمسيلة. ولقد توصل البحث إلى أن تطبيق طريقة التكلفة المستهدفة يساهم في تحديد فجوة التكلفة بينما تطبيق طريقة تحليل القيمة يساهم في امتصاص هذه الفجوة، بحيث تمكنت الشركة محل الدراسة من معالجة فجوة التكلفة بما يعادل تخفيض قدره 12 % من تكلفة المنتج، والتي تعد نسبة جد معتبرة نلمس تأثيرها الواضح على التكلفة النهائية للوحدة المنتجة ومن ثم على سعر بيعها وذلك مع المحافظة على جودة المنتج. This research aims to highlight the role of applying the target cost and value analysis methods to achieve the real reduction of the cost of products, by applying to a «HODNA LAIT» company in M’sila. This research concludes that the application of the target cost method contributes to identify the cost gap, while the application of the value analysis method contributes to absorb this gap, so that the company under study was able to address the gap between the target cost and the real cost and achieve a positive gap equivalent to a reduction of 12% The cost of the product, which is considered a very significant percentage, we see its obvious impact on the final cost price of the unit produced and then on the sale price while maintaining the quality of the product.
Keywords: محايبة التكاليف -- إدارة الإنتاج -- المؤسسات الاقتصادية -- الجزائر